2014
DOI: 10.1038/srep04656
|View full text |Cite
|
Sign up to set email alerts
|

Non-integrating gamma-retroviral vectors as a versatile tool for transient zinc-finger nuclease delivery

Abstract: Designer nucleases, like zinc-finger nucleases (ZFNs), represent valuable tools for targeted genome editing. Here, we took advantage of the gamma-retroviral life cycle and produced vectors to transfer ZFNs in the form of protein, mRNA and episomal DNA. Transfer efficacy and ZFN activity were assessed in quantitative proof-of-concept experiments in a human cell line and in mouse embryonic stem cells. We demonstrate that retrovirus-mediated protein transfer (RPT), retrovirus-mediated mRNA transfer (RMT), and ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 59 publications
2
18
0
Order By: Relevance
“…This optimized system efficiently delivered FLP recombinase and Sleeping Beauty (SB) transposase activity to target cells and was also successful in expressing biologically relevant amounts of ZFN [56]. Similar to the concept of repeated RET, repetitive transduction with RMT vectors increased the low ZFN activity obtained with a single administration [56].…”
Section: Retroviral Mrna Transfer (Rmt)mentioning
confidence: 92%
See 3 more Smart Citations
“…This optimized system efficiently delivered FLP recombinase and Sleeping Beauty (SB) transposase activity to target cells and was also successful in expressing biologically relevant amounts of ZFN [56]. Similar to the concept of repeated RET, repetitive transduction with RMT vectors increased the low ZFN activity obtained with a single administration [56].…”
Section: Retroviral Mrna Transfer (Rmt)mentioning
confidence: 92%
“…Inclusion of a posttranscriptional regulatory element (PRE) to improve RNA stability and expression levels [73], as well as codon optimization of the transgene along with introduction of an optimized Kozak consensus sequence for translation initiation further enhanced RMT potency [72]. This optimized system efficiently delivered FLP recombinase and Sleeping Beauty (SB) transposase activity to target cells and was also successful in expressing biologically relevant amounts of ZFN [56]. Similar to the concept of repeated RET, repetitive transduction with RMT vectors increased the low ZFN activity obtained with a single administration [56].…”
Section: Retroviral Mrna Transfer (Rmt)mentioning
confidence: 93%
See 2 more Smart Citations
“…Bobis-Wozowicz et al (2014) reported a versatile tool for ZFN protein delivery mediated by IDRV. In this case, although targeted gene knockouts in mammalian cells were possible, transgene insertion into a specific genomic locus was not reported.…”
Section: Discussionmentioning
confidence: 99%